2016
DOI: 10.1136/jclinpath-2016-203643
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node staging in prostate cancer: perspective for the pathologist

Abstract: Pelvic lymph node dissection (PLND) currently represents the gold standard method for nodal staging in the setting of localised prostate cancer and may also have a therapeutic benefit in certain patients. The histopathological evaluation of PLND specimens plays a critical role in accurate lymph node staging, however there is currently a lack of consensus regarding the optimum approach and no quality parameters are in place. In addition, there are no guidelines as to the handling of less commonly encountered no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Various minimal nodal yields have been proposed as a quality indicator for accurate LN staging following PLND; however, heterogeneity of studies in terms of surgical extent and pathological techniques make it difficult to define an appropriate threshold . In PCa, nodal counts ranging from 10 to >20 have been suggested, although a previous ISUP survey found that such nodal yields were not common in routine practice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various minimal nodal yields have been proposed as a quality indicator for accurate LN staging following PLND; however, heterogeneity of studies in terms of surgical extent and pathological techniques make it difficult to define an appropriate threshold . In PCa, nodal counts ranging from 10 to >20 have been suggested, although a previous ISUP survey found that such nodal yields were not common in routine practice .…”
Section: Discussionmentioning
confidence: 99%
“…The pathological assessment of PLND specimens plays a critical role in the evaluation of regional LNs. In addition to accurate nodal staging, other parameters, including LN density, metastatic tumour size and extranodal spread, may also have prognostic significance in patients with metastatic disease . Variations in pathology practice and methods of LN counting are known to influence LN yield, yet this parameter is often used as a surrogate marker for the adequacy and extent of surgical dissection both in clinical practice and the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, any differences in the dissection area and methods were negligible. There are no established guidelines regarding the optimum method of examining PLND specimens, and the approach may vary considerably between individual pathologists and institutions (20). At our institution, PLND specimens were processed using the same methods as the RP specimens.…”
Section: Standardmentioning
confidence: 99%
“…Méndez et al (2011) identified five genes (Receptor accessory protein (1REEP1), Ring finger protein 145 (RNF145), CTONG2002744, Myosin VA (MYO5A), and FBXO32) that were differentially expressed between node-positive and node-negative oral squamous cell carcinomas (OSCC), and suggested that this model is applicable for identification of occult metastasis in patients [ 46 ]. Similarly, studies on primary lung adenocarcinomas, pancreatic, breast, bladder, and prostate cancers models depicted a marked alteration in gene expression patterns along with a high relative risk of nodal involvement [ 47 , 48 , 49 , 50 , 51 ]. 4.…”
Section: Gene Expression Profilingmentioning
confidence: 99%